Majör yanıklı hastalarda erektil disfonksiyon: Takibin önemi Erectile dysfunction in patients with major burn injury: The significance of follow-up - ŞEKERCİ, ÇAĞRI AKIN; TANIDIR, YILÖREN; ÇAM, HAYDAR KAMİL (My University, 2022)
BACKGROUND: There were few prospective studies investigating the relationship between the burn injury and erectile dysfunction (ED). The aim of this study was to prospectively explore the alteration in erectile functions regarding major burn. METHODS: This study was conducted as a prospective survey in patients with major burn injury. The study group consisted of burn cases with at least 20% of body surface area affected according to the Wallace Rule of Nines. Initially International Index of ED-5 (IIEF-5) was administered to the patients in the burn unit, and it was repeated in the 2rd and 6th months. Burn types, the severity of burns, age of patients, and alteration in IIEF-5 scores were compared. RESULTS: The study included 63 male patients. The median age of the patients was 35 (20-73) years, and the median burn percent-age was 22 (20-60). The rate of ED was markedly increased during follow-up as 8%, 39.7%, and 25.4% at baseline, 3rd, and 6th month evaluation, respectively. The median initial IIEF-5 score of the patients was 23 (5-25). Subgroup analysis revealed that IIEF-5 score of patients with electrical and flame burn significantly decreased at 3rd month compared with the baseline values. The median IIEF-5 score of patients with electrical burn increased at 6th month compared with 3rd month (p=0.042). Binary logistic regression analysis showed that age and service period, and IIEF-5 Score at 3rd month and burn grade were all statistically significantly associated with the normal erectile function (IIEF-5>=18), at 3rd month and 6th month, respectively. CONCLUSION: The current trial demonstrated that IIEF-5 scores of patients with major burn can show significant impairment in long term, and it seems a time-dependent process. This is the first prospective trial showing that IIEF can be utilized to monitor erectile function of burn patients in a longer follow-up program.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Anesteziyoloji; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Anesthesiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ANESTEZİYOLOJİ; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; ANESTHESIOLOGY; EMERGENCY MEDICINE; Cerrahi; Anesteziyoloji ve Ağrı Tıbbı; Surgery; Anesthesiology and Pain Medicine